Security Threats Facing Southeast Asia - Ahmed , Alaa jabbar; Hashem, Nawar Jalil (The International and Political Journal, 2026)
Southeast Asian countries face numerous challenges in the geopolitics of war, including territorial disputes, competition for resources, and external interventions. The region is rich in natural resources, such as oil, gas, and minerals, which have attracted the attention of major powers, leading to tensions and the potential for conflict. In addition, long-standing territorial disputes, such as those in the South China Sea, pose a challenge to security, stability, and cooperation among countries in the region. The involvement of external powers, such as the United States and China, further complicates the geopolitical landscape, as these powers often have competing interests and may use their influence to support certain countries or positions. Finally, the potential for religious and ethnic tensions to escalate, as well as the threat of armed terrorist groups turning violent, is another challenge that must be addressed in the region